Population-level zoogeomorphology: the case of the Eurasian badger (Meles meles L.) - Coombes, M; Viles, H (Taylor and Francis, 2015)
The zoogeomorphological impact of burrowing animals varies in time and space as a result of the particular life history traits of the organisms involved, the patchy distribution of habitat resources, and fluctuations in population size. Such ecological complexity presents a major challenge for biogeomorphologists wishing to upscale from individuals to populations. Using a unique ecological data set for Eurasian badgers (Meles meles L.) in Wytham Woods, Oxfordshire, UK, we show that direct zoogeomorphological impact (soil displacement during sett excavation) is constrained by fluctuations in overall population size. Modeled digging rates for individual badgers (0.19-4.51 m3 yr-1) varied depending on the ecological function of the sett they are associated with, and we estimate that the whole population has displaced 304-601 ± 72 m3 of soil during the construction of 64 setts. This represents an overall excavation rate of 6.7-19.4 m3 (6.0-17.5 t) yr-1 in sett areas or 1.42-4.12 g m-2 yr-1 when averaged over the whole 424 ha woodland. As well as direct soil displacement, badger digging exposes material that is initially susceptible to erosion by water relative to undisturbed and litter-covered soils. Over time, setts become stabilized, representing unique landforms that persist in the landscape for decades to centuries.